Antecedents of brand loyalty in the commercial airline industry : a case study in the Malaysian context - Mustapha, Hadj Smail (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
Building and maintaining long-term relationship with customers is a key element of the relationship marketing philosophy, this requires an understanding of the customerfirm interaction. The concept of brand loyalty can be employed to emphasis the attitudinal and behavioural aspects of this relationship. This study aims to investigate the antecedents of brand loyalty in the conventional airline industry in Malaysia and gain an understanding of the dimensions of brand loyalty. Moreover, it investigates the impact of customer satisfaction, service quality, perceived value and brand image on brand loyalty. In addition to this, the study follows the composite approach and proposes that brand loyalty consists of a behavioural dimension and attitudinal dimension. The questionnaire data was collected from 327 airline passengers travelling from and to Malaysia. Two-stage Structural Equation Modelling (SEM) was followed to test the research model and hypotheses of this study. Therefore, the analysis of data showed that the two dimension model of brand loyalty was significant indicating that brand loyalty consists of attitudinal and behavioural dimensions. Furthermore, it was found that there were significant relationships between the variables except for four paths. The four insignificant paths were the relationship between 'service quality and attitudinal loyalty', 'airline image and customer satisfaction', ' service quality and attitudinal loyalty through customer satisfaction' and 'airline image and attitudinal loyalty through customers satisfaction'. The results of testing the structural model also indicated that customer satisfaction mediates the relationship between perceived value and brand loyalty.